Getting Started with Open VMS system Management - Miller, David Donald (Digital Press, 2003)
The book is intended as a precursor to Baldwin's OpenVMS System Management Guide and various OpenVMS documents. Thus it refers the reader to other books for the detailed management steps. Getting Started with OpenVMS System Management is a great introduction to the material Steve Hoffman and Dave Miller are revising for the OpenVMS System Management Guide, 2E.